Production Functions: Entrepreneurial Sector of Russia’s Regions - Pinkovetskaia, Iuliia; Gromova, Tatiana; Nikitina, Irina (Journal of History Culture and Art Research, 2018)
In the context of transformation of the Russian economy there is an urgent need for accelerated development of small and medium enterprises. Solving this problem is very urgent in each of Russia’s regions. The aim of the study was to assess the two-factor production functions that describe the dependence of the volume of production (turnover) of small and medium enterprises on the wages of their employees and investments in fixed assets. The study was based on empirical spatial data characterizing the activities of medium enterprises, small enterprises and microenterprises. Official statistical information on 82 regions of Russia for 2016 was used. The study allowed to determine the factors influencing turnover of SMEs located in all regions, to prove the high quality of approximation of the initial data by the two-factor production functions, to prove that the economy of the Russian regions has not reached saturation with small and medium enterprises. The results of the study, namely new knowledge and tools for assessing production activities of small and medium enterprises in the regions, are of scientific and practical importance. They can be used in monitoring of business climate in regions, determining resource needs, as well as the implementation of the Russian strategy for its development up to 2030.